(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research suggests an enhanced hybrid DSTATCOM for reactive and harmonic power adjustment that is fuelled by solar energy. A series-connected capacitor at the front end of the voltage source inverter and an LCL passive filter is used to connect the solar system to the grid.